PELATIHAN DAN PENDAMPINGAN PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN MICROSOFT POWER POINT DAN CAMTASIA DI SMAMUHAMMADIYAH 11 KOTA PADANGSIDIMPUAN - Andes Fuady Harahap; Sahlan Tuah; Rizky Ariaji; Viva Mulyana (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2017)
Based on the analysis of the situation and the problems faced by the partners, the devotional team will provide a solution to overcome teacher difficulties in developing learning media. The solution will be in the form of training and mentor for teachers in developing learning media with software incombination with Microsoft PowerPoint and Camtasia. The results achieved in this IbM activity are (1) Positive feedback obtained from the school, teachers at SMA Muhammadiyah 11 Padangsidimpuan during the activity. (2) Increasing information on instructional media that can help learning materials for teachers. (3) Teachers can design instructional media that can be adapted to the circumstances surrounding environment. (4) The high motivation and demand for the development of lesson materials through the media more exciting learning.Keywords: Software On Combination Microsoft PowerPoint and Camtasia, Development of Learning Media.